2023
DOI: 10.1002/sus2.112
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐vacancy‐containing cerium oxide nanoparticle‐decorated nanonetwork‐structured carbon toward high‐performance lithium–sulfur batteries

Abstract: Lithium–sulfur (Li–S) batteries have been regarded as promising next‐generation energy‐storage devices owing to their inherently high theoretical energy density. Unfortunately, the poor capacity and cycling life caused by severe polysulfide shuttle effect and sluggish redox kinetics in sulfur cathodes greatly impede the practical application of Li–S batteries. Herein, a new class of nanonetwork‐structured carbon decorated with oxygen‐vacancy‐containing cerium oxide nanoparticles (NSC–CeO2−x), in which carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Relative to the GO-modified material, SnO 2– x is introduced to enhance the adsorption and catalysis of polysulfides. Compared with the NSC-CeO 2– x -modifying material, the PC carbon matrix has abundant pores, so it has a higher specific surface area, which is not only more conducive to the adsorption of polysulfides but also enables the uniform distribution of SnO 2– x in PC. Therefore, the battery with the SnO 2– x /PC-modified separator has better 1 C cycle performance and lower impedance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Relative to the GO-modified material, SnO 2– x is introduced to enhance the adsorption and catalysis of polysulfides. Compared with the NSC-CeO 2– x -modifying material, the PC carbon matrix has abundant pores, so it has a higher specific surface area, which is not only more conducive to the adsorption of polysulfides but also enables the uniform distribution of SnO 2– x in PC. Therefore, the battery with the SnO 2– x /PC-modified separator has better 1 C cycle performance and lower impedance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Therefore, the coordinated MÀ N 4 centers, especially FeÀ N 4 , CoÀ N 4 , and NiÀ N 4 stuctures have been widely explored in LiÀ S batteries. [26][27][28][29] However, the symmetric MÀ N 4 coordination structure shows a symmetric electron distribution at the metal center and results in near-vertical adsorption for polysulfide, therefore limiting the activation of reactants and conversion kinetics of polysulfide. [30][31][32] Heteroatoms with different atomic radii and electronegativity (such as B, O, F, P, and S, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Therefore, the coordinated MÀ N 4 centers, especially FeÀ N 4 , CoÀ N 4 , and NiÀ N 4 stuctures have been widely explored in LiÀ S batteries. [26][27][28][29] However, the symmetric MÀ N 4 coordination structure shows a symmetric electron distribution at the metal center and results in near-vertical adsorption for polysulfide, therefore limiting the activation of reactants and conversion kinetics of polysulfide. [30][31][32] Heteroatoms with different atomic radii and electronegativity (such as B, O, F, P, and S, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the monodisperse dispersed metal atoms with N coordination (M−N 4 ) can build atomic‐level contact/catalytic interfaces for accelerating liquid‐solid and solid‐solid conversion [19–25] . Therefore, the coordinated M−N 4 centers, especially Fe−N 4 , Co−N 4 , and Ni−N 4 stuctures have been widely explored in Li−S batteries [26–29] . However, the symmetric M−N 4 coordination structure shows a symmetric electron distribution at the metal center and results in near‐vertical adsorption for polysulfide, therefore limiting the activation of reactants and conversion kinetics of polysulfide [30–32] .…”
Section: Introductionmentioning
confidence: 99%